2004
DOI: 10.1002/masy.200450609
|View full text |Cite
|
Sign up to set email alerts
|

ω‐substituted long chain alkylphosphonic acids – their synthesis and deposition on metal oxides and subsequent functional group conversion of the deposited compounds

Abstract: The crystal structure and the surface of alumina layers on silicon wafers were investigated by means of GIWAXS, WAXS, and AFM. Self‐assembled monolayers of ω‐substituted long‐chain alkylphosphonic acids were deposited on alumina and the layer thickness and homogeneity were determined by ellipsometry revealing a dependency of thickness and homogeneity on the nature of the substituent. During the adsorption process surface etching by the phosphonic acid was observed causing an increase in surface roughness.Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The graing of alkylphosphonic acids or derivatives has been widely described in the literature. [16][17][18][19][20] These molecules are made by a linear alkyl chain bearing a phosphonic acid group as chain end (CH 3 (CH 2 ) n P(O)(OH) 2 ). Aer graing, the obtained hybrid material got new properties such as hydrophobicity or corrosion resistance.…”
Section: Graing Of Alkylphosphonic Structures and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The graing of alkylphosphonic acids or derivatives has been widely described in the literature. [16][17][18][19][20] These molecules are made by a linear alkyl chain bearing a phosphonic acid group as chain end (CH 3 (CH 2 ) n P(O)(OH) 2 ). Aer graing, the obtained hybrid material got new properties such as hydrophobicity or corrosion resistance.…”
Section: Graing Of Alkylphosphonic Structures and Derivativesmentioning
confidence: 99%
“…Guerrero et al 41 identied bidentate species (19 ppm) but mainly highlighted tridentate bonding mode since they applied harsh graing conditions. 17 O NMR spectroscopy was also an interesting tool to study the chemical bonding but required 17 O enriched acid which is the main drawback of this technique. Two research teams 42,44 showed the possibility to distinguish P]O, P-O-H, P-O-Ti and TiO x bonds by this technique.…”
Section: Titanium Oxidementioning
confidence: 99%
“…In this work, we will focus on the adsorption of phosphonic acids on aluminum oxides. Although some reports exist on the formation of SAMs of phosphonic acids on the oxide of iron, silicon, , zirconium, and titanium, most of the work has been performed on aluminum oxide. Phosphonic acids bind with aluminum hydroxyl groups through an acid–base condensation elimination reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Alkylphosphonic acids have been shown to assemble on a number of oxide surfaces, such as tantalum oxides, aluminum oxides, silicon oxides, stainless steel oxides, and mica. [13][14][15][16][17][18][19][20][21][22][23][24] The phosphonic acids are mostly deposited from an organic or water-diluted (10 -3 mol/L) solution. It is known that the phosphonic acids interact with the aluminum hydroxyl groups, where an increase in the amount of surface hydroxyls enhances the phosphonic acid deposition.…”
Section: Introductionmentioning
confidence: 99%